Breastfeeding: Factors that lead to early weaning (Research, Society and Development, 2023)
Early weaning is a worrying factor, with the need to investigate and intervene in the reality of pregnant and postpartum women as early as possible in order to avoid mortality and morbidity, and to this end, it is up to the health professional, such as nurses, to promote, support and encourage the practice of exclusive breastfeeding. The present study aimed to identify in the scientific literature the main reasons associated with early weaning in children under six months of age. This is an Integrative Literature Review, in which articles were selected through the Scielo (Scientific Electronic Library Online) and Lilacs (Latin American and Caribbean Literature in Health Sciences) databases. The following keywords were used: “breastfeeding”, “weaning”, “pacifier”, “epidemiology”, with articles being filtered in the Portuguese language from 2017 to 2022. The main results found in the articles were that the majority of mothers receive guidance on breastfeeding in prenatal and postpartum consultations, but social factors and the introduction of other foods intensify early weaning. Through the study, it was concluded that both pregnant and postpartum women receive guidance on the importance of introducing breastfeeding and continuing it. And studies show that the majority end up introducing other forms of feeding due to social factors, such as introducing pacifiers and bottles early, thus confusing sucking and discontinuing breastfeeding.